Kajian fungsi sosial-budaya ruang terbuka hijau publik Kecamatan Serpong, Kota Tangerang Selatan - Hastita, Dinda Hindira; Yuslim, Silia; Luru, arselinus Nirwan (Jurnal Arsitektur Lansekap; Vol.6, No.2, Oktober 2020DO - 10.24843/JAL.2020.v06.i02.p15, 2020)
Study of the socio-cultural function of public green open space in Serpong District, South Tangerang City. Urban communities have a variety of activities and routines with high mobility. It takes a balance between busy activities and leisure activities where people have the freedom to communicate and interact in space. The area of public green open space in Serpong District has reached 28% of the total required by Law no. 26 article 29. Most of the green open space is located in certain housing areas, so that its utilization is more focused on residential residents. . Based on these facts, this study aims to discuss the extent to which the socio-cultural functions that must be carried out by public green open space outside of residential areas can meet the needs of people who live outside the existing residential areas. A study on the social functions of public green open space will be carried out in Serpong District, South Tangerang City, with samples of City Forest 2, Health Park, and Peace Park. This study used survey method using data collection instruments in the form of observations and questionnaires which were scored based on a Likert scale. Data analysis technique is using proportion (percentage) or frequency. From the research results, it is known that the social function of public green open space in City Forest 2, Health Park, and Peace Park has been achieved, namely as a communication medium for city residents, describing local cultural expressions, recreation areas, and educational and research facilities.